Trends in Basic and Therapeutic Options in HIV Infection Towards a Functional Cure - Bartholomew Okechukwu, Ibeh (IntechOpen, 2015)
The past decade has seen several changes in HIV prevention, transmission and therapeutic interventions to end the scourge. This book is a collection of expert assays on various aspects of HIV prevention, bioresource deployment, microbicides, host antiviral proteins, antiviral drug responses and novel treatment strategies for which there is evident need for scientific focus and review of the current trend. A visible objective of the book is to provide a wider readership of scientist, clinicians, social workers/HIV caregivers, immunologist, postgraduate students, trainers and vaccine developers an informative and multidisciplinary approach to HIV treatment and intervention strategy by presenting current trends in the development of therapeutic options and its attendant challenges. Practical and informative, the book provides state-of-the-art information on dynamics of HIV distribution, transmission, therapeutic measures and functional cure.